(untitled) (Research, Society and Development, 2022)
Leifsonia xyli subsp. xyli, the causal agent of ratoon stunting, is an endophytic bacteria that colonize sugarcane xylem vessels. It is generally accepted that sugarcane is the only natural host of ratoon stunting. The objective of this work was to investigate the presence of bacteria in insects associated with sugarcane in an experimental area cultivated with four varieties. The plants were artificially inoculated with bacteria, the samples of insects were collected from the sugarcane crop. Specific PCR was used with DNA extracted from different insect parts (head, abdomen, or whole-body). The DNA of the bacterium was not detected in those investigated insects, confirming that the host range of the bacterium is restricted to Saccharum spp.